(NmEHANOGIDROLITI^ESKIE PROCESSY I PRO^NOSTX TWERDYH TEL (B/s - (NbER[TEJN(B, (NwLADIMIR aBRAMOWI^s ((NlENINGRAD (B:s (NnAUKA(B. (NlENINGR(B. (NOTD(B-(NNIE(B,s, 1987)
(NbIBLIOGR(B. 498 (NNAZW(B.s
Keywords: (NwLIQNIE WLAVNOSTIs; (NpRO^NOSTXs; (NtWERDYE TELAs